Mouse inoculation for the detection of non-cultivable gastric tightly spiralled bacteria - Mendes,E.N. (1998)
In the present study we compared the inoculation of swine gastric mucus into the stomach of mice, the urease test and carbolfuchsin-stained smears for the diagnosis of the infection with "Gastrospirillum suis" ("Helicobacter heilmannii" type 1), an uncultivated tightly spiralled gastric bacterium. Fragments obtained from the antral and oxyntic mucosa of the stomach of 50 slaughtered pigs were used for urease test, for carbolfuchsin-stained smears and for obtaining scrapings of mucus for mouse inoculation. The mice were killed by spinal dislocation 10 days after inoculation and fragments of the antral and oxyntic mucosa were used for spiral bacterium identification (urease test and carbolfuchsin-stained smears). Among the methods employed for the diagnosis of "H. heilmannii" infection, the inoculation of gastric mucus into the stomach of mice was the most sensitive and demonstrated bacterial positivity in 31 (62.0%) swine. Direct examination showed tightly spiralled bacteria in the gastric mucosa of only 4 (8.0%) of the 50 pigs studied. Among them, 3 (6.0%) presented a positive preformed urease test. Spiral bacteria were not seen in the gastric mucosa of any control mice. These results show that the use of the mouse inoculation method improved the detection of "H. heilmannii" in swine